Internalisasi Nilai Islami Via Permainan Puzzle pada Anak Usia Dini di Tadika Mutiara Qysara Malaysia - Saida Rahma; Zuliana Zuliana (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Tarbiyah dan Keguruan, Universitas Islam Bandung., 2026)
This study aims to analyze the process of internalizing Islamic values through puzzle-based activities among early childhood learners at Tadika Mutiara Qysara, Malaysia. The study employed a qualitative approach with a descriptive research design. The research informants consisted of teachers and students selected through purposive sampling. Data were collected through observation, interviews, and documentation and were subsequently analyzed through the stages of data reduction, data display, and conclusion drawing. The findings reveal that the internalization of Islamic values occurred through three stages: planning puzzle media containing Islamic values, implementing learning activities under teacher guidance, and habituating these values in daily activities. The values developed included aspects of faith, worship, and social morality, such as honesty, responsibility, cooperation (ta‘awun), and discipline. The novelty of this study lies in its model of Islamic value internalization through the stages of planning, implementation, and habituation, which are systematically integrated into puzzle media as a learning strategy in early childhood education institutions.